2008
DOI: 10.1161/circresaha.108.180984
|View full text |Cite
|
Sign up to set email alerts
|

RGS4 Regulates Parasympathetic Signaling and Heart Rate Control in the Sinoatrial Node

Abstract: Abstract-Heart rate is controlled by the opposing activities of sympathetic and parasympathetic inputs to pacemaker myocytes in the sinoatrial node (SAN). Parasympathetic activity on nodal myocytes is mediated by acetylcholinedependent stimulation of M 2 muscarinic receptors and activation of G␣ i/o signaling. Although regulators of G protein signaling (RGS) proteins are potent inhibitors of G␣ i/o signaling in many tissues, the RGS protein(s) that regulate parasympathetic tone in the SAN are unknown. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 39 publications
9
106
2
Order By: Relevance
“…It will be interesting to use our model to investigate possible sources of constitutive K ACh channel activity-activation of K ACh channels by GTP in the absence of ACh (Ito et al 1991) and the loss of Ca 2+ -CaM regulation of RGS proteins might prove to be attractive targets for further investigation. In which context it is interesting to note that knock-out of the RGS4 protein abolished desensitization of the response to ACh in the SA node in mice (Cifelli et al 2008). A major limitation of the model presented here is that it cannot reproduce desensitization, and this after considerable effort.…”
Section: Discussionmentioning
confidence: 92%
“…It will be interesting to use our model to investigate possible sources of constitutive K ACh channel activity-activation of K ACh channels by GTP in the absence of ACh (Ito et al 1991) and the loss of Ca 2+ -CaM regulation of RGS proteins might prove to be attractive targets for further investigation. In which context it is interesting to note that knock-out of the RGS4 protein abolished desensitization of the response to ACh in the SA node in mice (Cifelli et al 2008). A major limitation of the model presented here is that it cannot reproduce desensitization, and this after considerable effort.…”
Section: Discussionmentioning
confidence: 92%
“…À/À mice to be dependent on RGS4 (Cifelli et al, 2008). This shows that RGS protein inhibitors may be used in a clinical setting alone or in conjunction with other therapies.…”
Section: Advances In Rgs Protein Drug Discovery -From Biochemical Actmentioning
confidence: 90%
“…Yet other studies in hearts overexpressing RGS4 found rapid cardiac dilation and marked mortality upon pressure overload induction (11), highlighting a complex role. This was further demonstrated by the recent discovery that RGS4 regulates parasympathetic (G α[i/o] ) signaling to control heart rate in the sinoatrial node (12).…”
Section: Introductionmentioning
confidence: 95%